2007
DOI: 10.1152/ajpheart.00047.2007
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of coronary reserve by ivabradine-induced reduction in heart rate in infarcted rats is associated with decrease in perivascular collagen

Abstract: Dedkov EI, Zheng W, Christensen LP, Weiss RM, MahlbergGaudin F, Tomanek RJ. Preservation of coronary reserve by ivabradine-induced reduction in heart rate in infarcted rats is associated with decrease in perivascular collagen. Am J Physiol Heart Circ Physiol 293: H590-H598, 2007. First published March 23, 2007; doi:10.1152/ajpheart.00047.2007.-We tested the hypothesis that chronically reducing the heart rate in infarcted middle-aged rats using ivabradine (IVA) would induce arteriolar growth and attenuate peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
75
2
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(88 citation statements)
references
References 29 publications
9
75
2
2
Order By: Relevance
“…In this study, ivabradine was shown to reduce heart rate in a mouse model of reperfused MI to a degree similar to previously studied animal models 15, 17. We also believe this to be the first report of mouse echocardiography performed after lateral thoracotomy via the third intercostal space.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In this study, ivabradine was shown to reduce heart rate in a mouse model of reperfused MI to a degree similar to previously studied animal models 15, 17. We also believe this to be the first report of mouse echocardiography performed after lateral thoracotomy via the third intercostal space.…”
Section: Discussionsupporting
confidence: 83%
“…These studies have also shown post‐MI ivabradine treatment to attenuate increases in LV end‐diastolic pressure17 and reduce markers of neuroendocrine activation 14. These effects are likely a combination of the direct effects of ivabradine treatment as well as downstream effects of improved remodeling.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Also, serum levels of CK-MB, hs-CRP and cTnI and infarct size % in this group were significantly lower than that of the control MI group. These results are consistent with that obtained by Dedkov et al [40] , Dominguez-Rodriguez et al [41] , Heusch et al [42] , Monnet et al [43] and Vilaine et al [44] . The mechanism of the cardioprotective effect of ivabradine could be self-explained in the present study by its significant HR reduction, significant decrease of the apoptotic factor Bax and significant increase of the antioxidant markers SOD& GSH.…”
Section: Shireen Sami Mahmoud ; Et Al…supporting
confidence: 92%
“…Studies were performed in animal models to assess whether selective pharmacological intervention able to control heart rate were able to revert and/or ameliorate functional remodeling of ventricular tissue in cardiac diseases. In a rat model of myocardial infarction it was documented that reduction of heart rate with a www.intechopen.com selective bradycardic agent (ivabradine, see below for further details) is able to improve maximal myocardial perfusion and coronary reserve (Dedkov et al, 2007). On the basis of this evidence, we tested whether heart rate reduction with ivabradine in post-infarcted rats could counteract the electrophysiological remodeling of ventricular myocytes.…”
Section: Pharmacological Modulation Of Funny Channels In the Heartmentioning
confidence: 99%